Tobacco, Alcohol, and Cancer in Low and High Income Countries - Yuan-Chin Amy Lee; Mia Hashibe (Ubiquity Press, 2014)
Background: Tobacco use is a well-established risk factor for cancers of the lung, head and neck, nasopharynx, esophagus, stomach, pancreas, liver, kidney, bladder, leukemia, and cervix. Alcohol consumption is a well-established risk factor for cancers of the head and neck, esophagus, liver, colorectum, and breast for women only. The majority of studies on tobacco and alcohol were conducted in high-income countries (HICs). Objective: The aim of this review was to assess the extent of tobacco and alcohol usage and to compare the cancer burden between low- and high-income regions. Findings: Overall, tobacco smoking is estimated to account for 21% of cancer deaths worldwide (29% in HICs and 18% in low- and middle-income countries [LMICs]). Alcohol consumption is estimated to account for 5% of all cancer deaths worldwide, with similar proportions in LMICs. Cancers of the breast, lung, stomach, liver, head and neck, esophagus, cervix, and nasopharynx, and leukemia are already diagnosed in greater numbers each year in less-developed countries compared with more developed countries. The future burden of tobacco- and alcohol-related cancers on less-developed regions is expected to increase greatly based on demographic effects, with a 69.9% increase in tobacco-related cancer cases and a 68% increase in cancers related to alcohol. Although HICs have experienced a decrease in tobacco prevalence in recent decades, LMICs are still in the early stages of the tobacco epidemic. Conclusion: Tobacco use and alcohol consumption will clearly remain important risk factors that must be targeted with public health efforts particularly in LMICs.